2011
DOI: 10.1016/j.bpj.2011.07.030
|View full text |Cite
|
Sign up to set email alerts
|

PAR-3 Oligomerization May Provide an Actin-Independent Mechanism to Maintain Distinct Par Protein Domains in the Early Caenorhabditis elegans Embryo

Abstract: Par proteins establish discrete intracellular spatial domains to polarize many different cell types. In the single-cell embryo of the nematode worm Caenorhabditis elegans, the segregation of Par proteins is crucial for proper division and cell fate specification. Actomyosin-based cortical flows drive the initial formation of anterior and posterior Par domains, but cortical actin is not required for the maintenance of these domains. Here we develop a model of interactions between the Par proteins that includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
93
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 53 publications
6
93
0
Order By: Relevance
“…We found that reducing the levels of active CDC-42 via cgef-1 mutation during polarity maintenance results in a substantial decrease in cortical myosin, even in par-6 mutants, suggesting that CDC-42 has two separable functions in polarity maintenance. In contrast to the role of CDC-42 in binding to PAR-6, the role of CDC-42 in cortical myosin regulation via MRCK-1 during polarity maintenance appears to be dispensable, consistent with the observation that the actomyosin cytoskeleton is not required for the maintenance of distinct cortical domains (Dawes and Munro, 2011;Goehring et al, 2011a;Goehring et al, 2011b).…”
Section: Research Articlesupporting
confidence: 79%
See 2 more Smart Citations
“…We found that reducing the levels of active CDC-42 via cgef-1 mutation during polarity maintenance results in a substantial decrease in cortical myosin, even in par-6 mutants, suggesting that CDC-42 has two separable functions in polarity maintenance. In contrast to the role of CDC-42 in binding to PAR-6, the role of CDC-42 in cortical myosin regulation via MRCK-1 during polarity maintenance appears to be dispensable, consistent with the observation that the actomyosin cytoskeleton is not required for the maintenance of distinct cortical domains (Dawes and Munro, 2011;Goehring et al, 2011a;Goehring et al, 2011b).…”
Section: Research Articlesupporting
confidence: 79%
“…We propose that the two effects exert unequal influence on polarity maintenance and that suppression of PAR-2 by CGEF-1 occurs because reduced active CDC-42 will restore the balance between the antagonistic forces of the anterior and posterior domains. Lowering MRCK-1 levels lowers the levels of cortical myosin in the anterior (Kumfer et al, 2010) but appears to have no effect on the size of the PAR-6 domain, consistent with the observation that the actomyosin cytoskeleton is not required for the maintenance of distinct cortical domains (Dawes and Munro, 2011;Goehring et al, 2011a;Goehring et al, 2011b). As mentioned above, however, the ability of mrck-1(RNAi) to partially block LGL-1 overexpression rescue of par-2 argues that MRCK-1 normally contributes to maintaining the anterior cortical domain, although this contribution is nonessential in a normal genetic background.…”
Section: Putting It All Togethersupporting
confidence: 79%
See 1 more Smart Citation
“…We focus on how protein abundance influences the behaviour of both the deterministic and stochastic versions of the model. In Dawes & Munro (2011), it was found that bistable behaviour in the temporal model of Par protein led to the existence of complementary domains in the corresponding spatio-temporal model. Here, we find that the corresponding temporal stochastic model permits switching behaviour (the model solution 'jumps' between steady states) for lower protein abundances, whereas for higher protein abundances the stochastic and deterministic models are in good agreement (the model solution evolves to one of two steady states).…”
mentioning
confidence: 99%
“…A key player in this process is the Par protein family whose asymmetric localization to anterior and posterior parts of the cell is crucial for proper division and cell fate specification. In this paper, we explore a stochastic analogue of the temporal model of Par protein interactions first developed in Dawes & Munro (Dawes and Munro 2011 Biophys. J.…”
mentioning
confidence: 99%